The Effect of Motivation and Work Spirit on Employee Performance in PT Sapadia Wisata Rantauprapat - Dimas Anggara; Bayu Eko Broto; Aulia Indra (Quantitative Economics and Management Studies, 2022)
This study aims to analyze the effect of motivation and work spirit towards employee performance because a high level of employee performance is needed in a company in order to achieve the goals set by the company. By having a high level of performance, employees will be able to overcome and solve problems that will be faced when carrying out their duties and obligations at work. And vice versa if the employee has a low level of performance then the employee will not be able to solve a problem or difficulty in carrying out his work. With high performance owned by employees, employees will be able to work optimally and help each other together in completing work that requires more energy and time. Basically, employee performance is the result of the process of the employee's personal self as well as the efforts of the company. The high performance of employees is an expectation for all companies or institutions that employ them.